Hedge fund crisis and financial contagion: evidence from long-term capital management - Halstead, John M; Hegde, Shantaram P; Klein, Linda S (The Journal of Alternative Investments, 2005)
Keywords: dept.eco; dept.fin

Monetary policy, composite leading economic indicators and predicting the 2001 recession - Mostaghimi, M (Journal of Forecasting, 2004)
On 26 November 2001, the National Bureau of Economic Research announced that the US economy had officially entered into a recession in March 2001. This decision was a surprise and did not end all the conflicting opinions expressed by economists. This matter was finally settled in July 2002 after a revision to the 2001 real gross domestic product showed negative growth rates for its first three quarters. A series of political and economic events in the years 2000-01 have increased the amount of uncertainty in the state of the economy, which in turn has resulted in the production of less reliable economic indicators and forecasts. This paper evaluates the performance of two very reliable methodologies for predicting a downturn in the US economy using composite leading economic indicators (CLI) for the years 2000-01. It explores the impact of the monetary policy on CLI and on the overall economy and shows how the gradualness and uncertainty of this impact on the overall economy have affected the forecasts of these methodologies. It suggests that the overexposure of the CLI to the monetary policy tools and a strong, but less effective, expansionary money policy have been the major factors in deteriorating the predictions of these methodologies. To improve these forecasts, it has explored the inclusion of the CLI diffusion index as a prior in the Bayesian methodology. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: Bayesian probability forecasting; Classical statistical decision theory; Composite leading indicators; Composite leading indicators (CLI); Composite leading indicators diffusion index; Diffusion index; Geochronology; Industrial economics; Information theory; Monetary policy; Predicting recessions; Probability; Public policy; Quality control; Set theory; Statistical methods; US economy; Us economy; dept.eco; dept.fin

Orange county bankruptcy: financial contagion in the municipal bond and bank equity markets - Halstead, John M; Hegde, Shantaram P; Klein, Linda S (The Financial Review, 2004)
We examine the spillover wealth effects of the Orange County, California bankruptcy announcement in December 1994 on municipal bonds, municipal bond funds, and bank stocks. This bankruptcy is prominent because of unprecedented losses and because it was caused by a highly leveraged derivatives strategy rather than a shortage of tax revenues and excess spending. We find contagion in the bond market with significantly negative abnormal returns for municipal bond funds without direct exposure to Orange County and for non-Orange County municipal bonds. In addition, our findings suggest the contagion spills over to the common stocks of investment and commercial banks that deal in or use derivatives; however, the equities of banks unexposed to derivatives are not affected. © 2004 Blackwell Publishing Ltd.
Keywords: Bank equity; Contagion; Derivatives; Fixed income; G2/H3/K2; Municipal financing; dept.eco; dept.fin

Currency substitution: evidence from latin america - Prock, Jerry; Soydemir, Gokce; Abugri, Benjamin A (Journal of Policy Modeling, 2003)
Currency substitution represents a shift from domestic currency to foreign currency and is often related to times of high and variable inflation. In this paper, we investigate the extent of currency substitution in Argentina, Brazil and Mexico using a vector error correction (VEC) model. We empirically test this hypothesis by introducing artificial shocks to the system of equations and find that M1 response to a one standard deviation increase in that country's interest rate is negative and significant for Argentina and Brazil but not for Mexico. An artificially introduced one standard deviation increase in nominal exchange rate results in a statistically significant increase in M1 in Argentina and Brazil but again not for Mexico. Based on the patterns of the impulse response functions (IRFs) and the magnitude of the coefficients, we conclude that currency substitution occurs to a greater extent in Argentina and Brazil than Mexico. This is reflective of the implementation of relatively more credible macroeconomic policies in Mexico after the December 1994 crisis. Thus from a policymaking perspective, it is important to consider that the greater the degree of currency substitution, the more sensitive a country's monetary aggregates are to sudden movements in exchange rates, productivity and interest rates. (C) 2003 Society for Policy Modeling. Published by Elsevier Science Inc. All rights reserved.
Keywords: Currency; Latin America; Substitution; VEC; dept.eco; dept.fin

Book Review: Birthquake: the baby boom and its aftershocks. by diane j. macunovich. chicago: the university of chicago press, 2002. pp xiii, 314. 37.50 - Mills, Judith Woerner (The Journal of Economic History, 2003)
Keywords: book.review; dept.eco; dept.fin

Stability of the money demand function: evidence from Ghana - Andoh, SK; Chappell, D (Applied Economics Letters, 2002)
This paper estimates the demand for money (M2) in Ghana for the period 1960 to 1996. The hypothesis is that the different macroeconomic adjustment policies (privatization, removal of foreign exchange controls etc.) which began in the mid 1980s would alter the demand for money function. The results of the study clearly show a structural break in the demand for money function in 1983.
Keywords: dept.eco; dept.fin; peer-reviewed

In-class simulations of the iterated prisoner's dilemma game - Bodo, Peter (Journal of Economic Education, 2002)
The author developed a simple computer program for the in-class simulation of the repeated prisoner's dilemma game with student-designed strategies. He describes the basic features of the software and presents two examples for the use of the program in teaching the problems of cooperation among profit-maximizing agents.
Keywords: Computer simulation; Experiments; Prisoner's dilemma; Repeated games; dept.eco; dept.fin

Market efficiency and non-linear dependence in the Czech crown/US dollar foreign exchange market - Chappell, David; Eldridge, Robert M (Discussiones Mathematicae Probability and Statistics, 2002)
Keywords: dept.eco; dept.fin

Exchange rate adjustment in partially liberalized economy - Grubacic, Sanja (Economics of Planning, 2002)
This paper develops a model of exchange rate determination in partially liberalized post-socialist economy that operates under soft budget constraints in nontradable sectors. The model captures the factors that determine the evolution of a country's external balance during the initial phase of economic liberalization. Three types of disturbances are the center of analysis: liberalization of trade and foreign exchange regime, devaluation, and price liberalization. We show that the real exchange rate appreciation may either improve or worsen the trade balance depending on the sources of this appreciation. Thus, we argue that the real exchange rate cannot reflect true country's competitiveness unless all sectors are equally exposed to hard budget constraints. The model implications are further analyzed through the empirical evidence on the relationship between the real exchange rate and trade balance in three selected East European countries.
Keywords: Europe; Exchange rate; External balance; Liberalization; Post-socialist economy; Soft budget constraint; balance of trade; competitiveness; dept.eco; dept.fin; exchange rate; external balance; liberalization; post-socialist economy; real exchange rate; soft budget constraint

Soft-landing monetary policy, composite leading economic indicators, and predicting the 2001 recession - Mostaghimi, Mehdi (Social Science Research Network, 2002)
Keywords: dept.eco; dept.fin

Corporate groups, capital investments and stock returns in japan - Wei, Kuochiang; Xie, Feixue; Titman, Sheridan (APFA/PACAP/FMA International Finance Conference in Tokyo, Japan, 2002)
Keywords: dept.eco; dept.fin

Information collection strategic design in experts-assisted decision making paradigm - Mostaghimi, Mehdi (Group Decision and Negotiation, 2001)
In an experts-assisted decision making paradigm, the information collection design becomes a strategic variable under a weak assumption that the final decision is dependent on the design used to collect information as well. As a result, the same information of the experts and the decision maker about the problem can potentially produce different final decisions for different information collection designs. The implication is that a decision maker can strategically select a design which serves his/her objective. This paper uses a Bayesian estimation methodology for combining experts' information with the decision maker's prior. An information collection process is designed by setting constraints on this model. Several designs are developed here using such controlled factors as a one-stage versus a two-stage decision process, experts' rank ordering, and group versus individual lobbying/consultation. An example is provided to illustrate the applicability of the concept. It is shown that the information produced in the process of producing a decision can also give insights into the impacts of the decision maker and the experts on the decision.
Keywords: Bayesian method; Experts-assisted decision making; Information theory; Reaching a consensus; dept.eco; dept.fin; experts-assisted decision making; information theory; reaching a consensus

Emerging market hedge funds: Do they perform like regular hedge funds? - Abugri, Benjamin A; Dutta, Sandip (Journal of International Financial Markets, Institutions and Money, 2009)
In this study, we investigate whether the performance of emerging market hedge funds (EMHFs) follow a pattern similar to that reported for advanced market hedge funds. In contrast to the pre-2007 period, our results for the post-2006 period show that EMHFs exhibit performance patterns similar to those reported for hedge funds that focus on the developed markets. Unlike in the pre-2007 period, EMHFs in general do not exhibit significant exposure to specific asset classes in the post-2006 period. On a risk-adjusted basis, we find that EMHFs do not consistently outperform the benchmarks. The reported performance patterns may provide useful insights to both academics and portfolio managers.
Keywords: Emerging market hedge funds; Hegde funds; Modified Sharpe Ratio; Portfolio performance measures; Risk-adjusted returns; dept.fin